An evaluation of the lighting environment in the public space of shopping centres. (April 2017) - Jin, Hong; Li, Xinxin; Kang, Jian; Kong, Zhe
Abstract: Interior lighting quality influences people's visual comfort and satisfaction with a space. Based on a field study about the effects of lighting environments on occupancies in eight shopping malls with three different latitudes and a wide range of size from 30, 000 to 210, 000 m 2 all over China, this study investigates the differences in subjective evaluations, the correlations between the lighting environments of public spaces and people's evaluations, and the regressions of scene mean luminance. A questionnaire survey and HDR-image techniques have been used to gather subjective feedback and collect physical lighting data. The results show that the subjective evaluations among different groups (gender, age, education background, and duration of stay in the shopping malls) are similar. The existence of daylighting plays an important role in subjective satisfaction, but not crucial enough to their brightness perception. The mean luminance values of these scenes are closely correlated to the diversity of the subjective evaluations. For shopping centres, the optimal L mean value is 1000 cd/m 2 for a mixed daylighting and artificial lighting environment, and 75 cd/m 2 as the recommended L mean value for an artificial lighting environment. Highlights: Lighting environment in shopping centres evaluated based on survey and measurement. Differences by user characteristics generally insignificant, except education level. The scene mean luminance is most appropriate metric to estimate users' responses. The values of the metric corresponding to subjective evaluations are proposed.